Financial inclusion and the goal of distributive justice in Islamic economics - Dzulkepli, Suziraha; Barom, Mohd Nizam (USIM Press, 2021)
The unprecedented level of income inequality and wealth concentration throughout the world today has pose a foremost challenge in the efforts towards realising inclusive and sustainable development. One of the means to achieve this 2030 Agenda that has been strongly promoted by the international community is through the concept of financial inclusion. The dimensions of financial inclusion, which include access, usage and quality of financial services for all have been demonstrated to have positive impacts on increasing the ability of the poor and underprivileged groups to improve their economic well-being. Additionally, the literature has also identified two additional financial inclusion features of Islamic finance namely risk-sharing and redistribution, which can further contribute to the goal of distributive justice as aspired in Islamic economics. Nevertheless, despite the numerous works on financial inclusion and distributive justice in the literature of Islamic economics and finance, a specific framework to link financial inclusion with the goal of distributive justice is still absent in the literature. Therefore, the objective of this paper is to conceptualize a framework that links the dimensions of financial inclusion with the three phases of realising distributive justice, i.e. pre-production, post-production, and redistribution. This conceptual framework provides the necessary theoretical foundation and operational guideline for the promotion of financial inclusion as part of the efforts towards realising the goal of distributive justice in Islamic economics.